The double-yolked egg: from the 'miracle of packaging' to nature's 'mistake'. Issue 1 (2nd January 2020) - Salamon, Attila; Kent, John P.
SUMMARY: Double-yolked (DY) eggs have been mostly described in domestic precocial species, and are rarely found in nature. It is estimated that 1–3% of domestic hen and duck eggs are DY. They occur when two yolks are encapsulated in a single shell and therefore differ from single yolked (SY) eggs in their external and internal characteristics. In previous decades DY eggs were distinguished from SY eggs only by their external characteristics, and this proved to be erroneous, as over 40% of DY eggs have similar size and shape to SY eggs. The internal characteristics of DY eggs constrain their fertility, as the yolks tend to be smaller, are probably ovulated earlier and are thus immature, having a significant negative impact on their reproductive potential. Further, the presence of a second yolk facilitates additional albumen secretion with the size of each yolk determining the additional amount secreted. This creates a primacy effect, whereby the first yolk in the oviduct could be fertilised, but the second may not be. The unique yolk and embryo positioning are associated with low hatchability. These factors reduce the reproductive potential of DY egg yolks individually or cumulatively. This supports the view that DY eggs are nature's 'mistake' and are viewed here as an extreme end of the normal distribution of variation and is unlikely to evolve further in avian species. However, there is still potential for further non-invasive research using DY eggs, especially in studies of factors affecting fertility.